Trends Research Project Based Learning (PjBL) Model to Improve Science Process Skills in Students' Science Learning (2015-2024): A Systematic Review - Nurasyah Dewi Napitupulu; Juniar Hutahaean; Asri Nur Lathifah Fauziyyah (Postgraduate, University of Mataram, 2024)
Science process skills are very important for students to apply scientific methods and develop knowledge in order to gain new knowledge or enrich existing knowledge. Science process skills can be facilitated through learning with a Project Based Learning (PjBL) model. This research aims to identify and analyze research trends of PjBL model to improve science process skill in science learning. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research on PjBL model to improve science process skill in science learning that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend on PjBL model to improve science process skill in science learning indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. However, in 2024 there will be a decline in the research trend on it. There are many documents in the form of articles, proceedings, chapters, preprints and edited books that discuss research into the PjBL model to improve science process skill in science learning. Key words that are often used in research about it are local wisdom, inquiry model, PBL, scientific attitude, etc.